2022
DOI: 10.3390/life12060799
|View full text |Cite
|
Sign up to set email alerts
|

The Endoplasmic Reticulum Cargo Receptor FgErv14 Regulates DON Production, Growth and Virulence in Fusarium graminearum

Abstract: Fusarium graminearum is a plant filamentous pathogenic fungi and the predominant causal agent of Fusarium head blight (FHB) in cereals worldwide. The regulators of the secretory pathway contribute significantly to fungal mycotoxin synthesis, development, and virulence. However, their roles in these processes in F. graminearum remain poorly understood. Here, we identified and functionally characterized the endoplasmic reticulum (ER) cargo receptor FgErv14 in F. graminearum. Firstly, it was observed that FgErv14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…In the liquid medium, the spore-emerging mycelium also does not extend polarly as in the control strain. Deletion of FgErv14 in F. graminearum also results in a similar phenotype ( Sun et al, 2022 ). Moreover, we identify some proteins’ role in the establishment of cell polarity in the interactome and proteome, although without further validation.…”
Section: Discussionmentioning
confidence: 92%
“…In the liquid medium, the spore-emerging mycelium also does not extend polarly as in the control strain. Deletion of FgErv14 in F. graminearum also results in a similar phenotype ( Sun et al, 2022 ). Moreover, we identify some proteins’ role in the establishment of cell polarity in the interactome and proteome, although without further validation.…”
Section: Discussionmentioning
confidence: 92%
“…Unexpectedly, although the absence of full‐length FgGga1 disrupted TGN‐to‐PM transport, the deletion of any of the five domains did not affect TGN‐to‐PM trafficking, suggesting the functional redundancy of FgGga1 domains in regulating TGN‐to‐PM transport. Vascular trafficking regulators of different organelles have been widely reported to be involved in the vegetative growth and virulence of F. graminearum , such as FgErv14 and FgRab1 (Sun et al, 2022; Zheng et al, 2015), which are the regulators of transport between ER and Golgi apparatus; and FgRab6 (Zheng et al, 2015), which is the regulator of intra‐Golgi transport, etc. It has also been reported that the TGN‐to‐PM transport regulators FgSec2A and FgRab8 (Sec4 in yeast) are necessary for vegetative growth and virulence in F. graminearum (Zheng, Li, et al, 2018); our finding that FgGga1‐mediated TGN‐to‐PM transport also plays a key role in vegetative growth and full virulence is in consistence with that.…”
Section: Discussionmentioning
confidence: 99%
“…FgErv14 was identified as an endoplasmic reticulum (ER) cargo receptor in F. graminearum. Two weeks after fertilization, the ∆fgerv14 mutant showed a complete absence of perithecia production [47]. Systematic investigation of Phox homology domaincontaining proteins in F. graminearum revealed that FgBem1 plays a crucial role in both sexual development and virulence.…”
Section: Genes Involves In the Formation Of Peritheciamentioning
confidence: 99%